Water‐soluble carbohydrates in Patzkea paniculata (L.): a plant strategy to tolerate snowpack reduction and spring drought in subalpine grasslands. (19th January 2020) - Bernard, L.; Decau, M.‐L.; Morvan‐Bertrand, A.; Lavorel, S.; Clément, J.‐C.
Abstract: In subalpine grasslands of the central French Alps, cessation of traditional mowing promotes dominance of Patzkea paniculata (L.) G.H.Loos ( Poaceae ) tussocks, with high biomass but low fodder quality. Mowing limits P. paniculata abundance through the depletion of its water‐soluble carbohydrate (WSC) reserves, which sustain early spring growth initiation. However, the effectiveness of mowing effects is modulated by grassland functional composition, fertilization and climate change, as WSC compounds, and notably fructans, support plant physiological responses to climate stresses such as drought or frost. To characterize the mechanisms underpinning the control of P. paniculata under global change, we tested the effects of climate manipulation (combined snow removal and drought) and management (cutting and fertilization) alone or in combination on P. paniculata WSC storage in assembled grassland communities of varying functional composition. Management and climate treatments individually decreased seasonal fructan storage, with neither additive nor synergic effects between them, primarily due to the dominance of management over climate effects. Fructan amounts were higher in individuals growing in unmanaged exploitative communities compared to unmanaged conservative communities, regardless of climate treatments, but management overrode these differences. Our findings suggest that reduction by combined snow removal and drought of P. paniculata carbon allocation to WSC storage may similarly limit its dominance to that in current mowing practices. Abstract : Our study suggests that the effects of climatic stress (i.e. early snow removal and drought) on Patzkea paniculata, and especially on its carbon allocation to water soluble carbon storage (notably fructans), limit its expansion similarly to traditional management in subalpine grasslands.